2020
DOI: 10.1002/adbi.201900285
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cytotoxicity of a Novel Trp‐Rich Peptide against Lung Tumor Spheroids Encapsulated inside a 3D Microfluidic Device

Abstract: There is a globally rising healthcare need to develop new anticancer therapies as well as to test them on biologically relevant in vitro cancer models instead of overly simplistic 2D models. To address both these needs, a 3D lung cancer spheroid model is developed using human A549 cells trapped inside a collagen gel in a compartmentalized microfluidic device and homogenously sized (35–45 µm) multicellular tumor spheroids are obtained in 5 days. The novel tryptophan‐rich peptide P1, identified earlier as a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…On day 5, the average diameter for the co-culture group was 44 mm, whereas it was only 38 mm for the monoculture group, indicating a significant increase of 15.7% (P< 0.005). The authors have shown in an earlier study that cancer cells do not migrate to form tumor spheroids; instead, they undergo proliferation to form cellular aggregates, as confirmed by non-significant variations in the total number of cellular aggregates [22]. Therefore, it can be concluded that most of the cell aggregates in the monoculture group had a slower growth rate compared with the co-culture groups and reached a diameter of >35 mm only after 5 days of culture.…”
Section: Growth Characterization Of Tumor Spheroids: Co-culture Accelerated Tumor Growthmentioning
confidence: 88%
See 4 more Smart Citations
“…On day 5, the average diameter for the co-culture group was 44 mm, whereas it was only 38 mm for the monoculture group, indicating a significant increase of 15.7% (P< 0.005). The authors have shown in an earlier study that cancer cells do not migrate to form tumor spheroids; instead, they undergo proliferation to form cellular aggregates, as confirmed by non-significant variations in the total number of cellular aggregates [22]. Therefore, it can be concluded that most of the cell aggregates in the monoculture group had a slower growth rate compared with the co-culture groups and reached a diameter of >35 mm only after 5 days of culture.…”
Section: Growth Characterization Of Tumor Spheroids: Co-culture Accelerated Tumor Growthmentioning
confidence: 88%
“…The SU-8 100 (MicroChem, Texas, USA) photoresist-based UV photolithography was used to generate a silicon-SU-8 (Si-SU-8) master that was then replica-molded to create polydimethylsiloxane (PDMS) (Sylgard 184; Dow Chemical Pty Ltd, Victoria, Australia) microfluidic chips, as described in the authors' previous work [22]. Briefly, after overnight silanization of the Si-SU-8 master using trichloro (1h,1h,2h,2h-perfluorooctyl)silane (Sigma-Aldrich, New South Wales, Australia), PDMS at a ratio of 1:10 was mixed, degassed and poured over the SI-SU-8 master and cured at 70°C for 6 h. The cured PDMS was then peeled off carefully, punched at the inlets/outlets, cleaned and dried.…”
Section: Microfluidic Device Fabricationmentioning
confidence: 99%
See 3 more Smart Citations